1999
DOI: 10.1177/107602969900500406
|View full text |Cite
|
Sign up to set email alerts
|

Mild Myocardial Stunning Affects Platelet Aggregation and Certain Hemostatic Factors in Swine

Abstract: Myocardial stunning is characterized by transient contractile dysfunction occurring subsequent to an episode of ischemia followed by reperfusion. Platelet activation and hemostatic abnormalities have been described in patients with unstable angina and acute myocardial infarction, however, their role in the pathogenesis of myocardial stunning is unknown. The purpose of this study was to determine if platelet aggregation and certain hemostatic factors change during myocardial stunning following brief coronary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The magnitude of these changes has been consistently found to correlate with the severity of the clinical manifestation of the acute coronary syndrome (1,10). Although limited, several animal experiments have shown that myocardial stunning after brief coronary occlusion is associated with substantial dynamic changes in platelet aggregability and other hemostatic factors (37). For example, inhibiting the activity of platelets, but not of neutrophils, improves contractile recovery from myocardial stunning (14).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of these changes has been consistently found to correlate with the severity of the clinical manifestation of the acute coronary syndrome (1,10). Although limited, several animal experiments have shown that myocardial stunning after brief coronary occlusion is associated with substantial dynamic changes in platelet aggregability and other hemostatic factors (37). For example, inhibiting the activity of platelets, but not of neutrophils, improves contractile recovery from myocardial stunning (14).…”
Section: Discussionmentioning
confidence: 99%
“…17) Serebruany, et al also reported that myocardial stunning after coronary ligation is associated with substantial dynamic changes in platelet aggregation and other haemostatic factors. 18) Moreover, many studies have illustrated that the addition of platelets to the perfusate impairs coronary blood flow, 19) decreases ventricular and postischemic contractile recovery, 20,21) and promotes the occurrence of life-threatening cardiac arrhythmia 22) in numerous models of myocardial RI.…”
Section: Discussionmentioning
confidence: 99%